Analisis Literatur Tentang Difraksi Dan Interferensi Dalam Teknologi Optik - Mendrofa, Valen Kurnia; Harefa, Manjaya (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Practical work has been carried out on the Application of Diffraction and Light Interference Phenomena in Measuring the diameter of thin objects. This practicum aims to understand diffraction events and light interference, understand the application of interference diffraction to measure the thickness of thin objects, and find out the factors that influence diffraction events and light interference. Diffraction and interference can occur simultaneously when light passes through a narrow slit or thin object and combines to form a new light wave. This practicum uses the principle of superposition of light waves, using light as a wave so that it can create superposition phenomena and their derivatives, namely diffraction and interference. This practicum can be done by preparing tools and materials, then arranging the tools and materials according to the scheme. Then the physical parameters in this experiment were measured and recorded, namely the distance from the laser to the object, the distance from the object to the screen, and the distance created between the light patterns and the central light. The variations used are variations in thin objects, namely guitar strings and copper cables and variations in the distance of the object to the screen. From the experiments that have been carried out it can be concluded that diffraction and light interference events are the nature of light as a wave which has the principle of superposition. By applying the phenomena of diffraction and interference, the diameter of an object can be determined. From the practicum that has been carried out, data is obtained in the form of distances between orders or light-dark patterns that are formed. For variations of guitar strings, the diameter is 0.13 mm. while for the copper cable variation, the diameter is found to be 0.77 mm.